A Comprehensive Overview of Online Resources to Identify and Predict Bacterial Essential Genes - Peng, Chong; Lin, Yan; Luo, Hao; Gao, Feng (Frontiers in Microbiology, 2017)
Genes critical for the survival or reproduction of an organism in certain circumstances are classiﬁed as essential genes. Essential genes play a significant role in deciphering the survival mechanism of life. They may be greatly applied to pharmaceutics and synthetic biology. The continuous progress of experimental method for essential gene identification accelerated the accumulation of gene essentiality data which facilitates the study of essential genes in silico. In this article, we present some available web resources related to gene essentiality, including bioinformatic software tools for transposon sequencing (Tn-seq) analysis, essential gene databases and online services to predict essential genes. We review several computational approaches that have been used to predict essential genes, and summarize the features used for gene essentiality prediction. In addition, we evaluate the available online essential gene prediction servers based on the experimentally validated essential gene sets of 30 bacteria from DEG. This article is intended to be a quick reference guide for the microbiologists interested in the essential genes.